Failure to thrive and it’s Risk factors among children under 5 years old in Al-Batool Teaching Hospital in Baquba city - Abdul Kareem Mahawi, Nadia; Ahmed Shakir , Shahab; Shamkhi Gebir , Mehdi (Diyala Journal of Medicine, 2022)
Background: Failure to thrive (FTT) indicates insufficient weight gain or absence of an appropriate physical growth,it is a sign not a disease ,commonly seen by the primary health care physicians. It might be due to organic or non-organic causes and it is usually of a multifactorial etiology. Objective: To detect the prevalence of failure to thrive and risk factors in pediatric age group - under 5 year old in Al-Batool teaching hospital in Baquba city through 2020-2021. Patients and Methods: This study was across sectional study that took place In Al-Batool Teaching Hospital for maternity and children,in Baquba Distract-Diyala province, Iraq.during the period from 1st of February 2020-31st of July 2021. Throughout this study Two hundred and fifty (250) child were randomly selected under -5years old . Informations were collected from the patients files including age,current weight,birth weight,type of feeding,weaning,history of prematurity, history of chronic diseases and socioeconomic conditions. Results: Showed that children below 12 months were (45.2%), males (51.6%)and females (48.4%). male:female ratio was 1:1 ,majority of children were from Bohris . medium socioeconomic level was the largest with (61.6%). regarding mother education,mothers who have secondary education represent the largest level with (45.6%),children with bottle feeding were the largest with (45.0%),premature birth represent (2.0%),children with chronic diseases (14.0%),children with UTI (32.0%). Children with (FTT)were(23.2%),while (76.8%) were of normal growth. Regarding age groups most of the affected children were below 24 months of age with (36.5%) (P value was 0.0001) which is considered to be a significant. Males with (FTT) (24.8%) ,while Females (21.5%). (Pvaluewas0.534) which is considered to be of no significance. Regarding children with (FTT) and low socioeconomic level it was (68.8%) (p value was 0.0001)which is considered to be a significant. Children with (FTT) and illutrate mother was(60.0%) (p value was 0.0001)which is considered to be a significant. children with breastfeeding showed no (FTT) ,while those with bottle feeding was (37.0%) (P value was 0.0001 ) which is considered to be a significant. children with (FTT) and UTI (58.8%)(P value was 0.0001)which is considered to be a significant. Conclusion: This study concluded that failure to thrive is strongly correlated with poverty, mothers education ,chronic diseases, premature birth and type of feeding.failure to thrive showed no correlation with gender .